Moral Value and Characters' Sense of Responsibility in J. K. Rowling’s The Christmas Pig - Watsiqoh, Tsamarah Nabilatul (English Literature Study Program, 2023)
The moral values are an issue that will continue to be discussed. The moral value emphasized in this research focused on the value of responsibility. The researcher chooses this moral value because The Christmas Pig is a fantasy novel that emphasizes how humans, especially children, should keep and take responsibility for their actions. This study aims to identify the moral value of responsibility along with the development of the characters’ sense of responsibility in the novel entitled The Christmas Pig written by J.K. Rowling. This research is a literary criticism study with structuralism approach by paying attention to intrinsic elements of the story. The study uses the concept of responsibility from Linda and Eyre, which distinguishes responsibility into four parts: responsibility to parents, responsibility to society, responsibility to self, and responsibility to others. The results of this study indicate that there are three kinds of moral values of responsibility portrayed, namely responsibility to parents, responsibility to society, and responsibility to self. Each of these moral values of responsibility is found in the main characters’ and minor characters, namely Jack and Holly. Furthermore, the development of the characters’ sense of responsibility is focused on Jack and Holly. Jack’s development of the characters’ sense of responsibility is portrayed through his action toward CP. Jack, who is initially being rude to CP, becomes a responsible child and takes care of CP. Meanwhile, Holly is portrayed through her irresponsible attitude such as selfishness, disobedience, and impulsiveness, turning into a child who is responsible for society, her parents, and herself. Overall, this thesis provides a deeper understanding of the moral value conveyed in The Christmas Pig and the importance of responsibility as a fundamental aspect of human life.